Paralogs vs. genotypes? Variability of Babesia canis assessed by 18S rDNA and two mitochondrial markers - Hrazdilová, Kristýna; Myśliwy, Izabella; Hildebrand, Joanna; Buńkowska-Gawlik, Katarzyna; Janaczyk, Bartłomiej; Perec-Matysiak, Agnieszka; Modrý, David (Veterinary parasitology, 2019)
Canine babesiosis caused by Babesia canis sensu stricto became an emerging disease of dogs across Europe calling for attention also in countries where it was an only rare imported disease. An easy accessibility of molecular methods and the growing amount of sequencing data led to the description of intraspecific variability in 18S rDNA sequences designated as "genotypes". Using material from a homogenous cohort of dogs with microscopically confirmed canine babesiosis caused by B. canis, we evaluated Babesia intraspecific variability and amplification sensitivity of three different genes (18S rDNA, COI, Cytb) to assess their potential as diagnostic or phylogenetic markers. In raw sequencing data obtained, we observed at least 3 ambiguous positions in up to 86% of chromatograms within the ∼560 bp fragment of 18S rDNA suggesting the existence of several, not identical copies of this gene. Our COI haplotype analysis resulted in a star-like pattern indicating a recent origin of most haplotypes, but not supporting the existence of two dominant haplotypes. Similarly, the Cytb sequences obtained from samples with all variants of 18S rDNA were identical. We corroborate previous observations from three other European countries and bring the evidence of the existence of 18S rDNA paralogs in B. canis genome replacing currently used "genotype" theory.
Keywords: Animals; babezióza; Genome, Protozoan; RNA, Ribosomal, 18S; Genotype; Europe; Mitochondria; nemoci psů; Evropa; genotyp; Dog Diseases; Dogs; genom protozoální; kohortové studie; mitochondrie; Genetic Variation; Phylogeny; Cohort Studies; Babesiosis; DNA, Protozoan; Haplotypes; protozoální DNA; RNA ribozomální 18S; Sequence Analysis, DNA; Babesia; zvířata; genetické markery; haplotypy; sekvenční analýza DNA; fylogeneze; genetická variace; psi; Genetic Markers